An annotated checklist of angiospermic flora of Rema-Kalenga Wildlife Sanctuary (Habiganj) in Bangladesh II.a: Magnoliopsida (Dicots) - Uddin, Mohammad Zashim; Hassan, Md Abul; Khan, Md Salar (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(1): 79-94, 2003 (June)